Tahfizh Al-Qur'an Learning Model in The Bilingual Class System (BCS) of Tahfizh Science Program at MAN 2 Kudus - Choeroni Choeroni; Fattah Syukur; Hamdan Hadi Kusuma (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
This article is aimed to investigate Tahfizh al-Qur'an learning model in the Billingual Class System (BCS) of Tahfizh Science Program at MAN 2 Kudus. This study tries to examine Tahfizh al-Qur'an learning model in Madrasah in order to enable it as beneficial as a Tahfizh al-Qur'an learning model for educational institutions which are based on Tahfizh al-Qur'an boarding schools, particularly for State Aliyah Madrasah as well as to give impacts on Development Model of Madrasah grounded in Tahfizh al-Qur'an Pesantren to creat tafaqquh fiddin scholars who are not only capable in the fields of science and technology, but also in the Qur'an memorization. The method used in this research is field research with a qualitative descriptive analysis approach. The results showed that there was an integration between the learning in the tahfizh al-Qur'an boarding school and the learning in the formal Madrasah classes with a regular schedule and with intensive guidance for memorization targets at each level. The study can be concluded that by using the BIHIM HUFADZE model, which stands for guidance (Bimbingan), intensive (Intensif), halaqah (Halaqah), integration (Integrasi), madrasah (Madrasah), memorizing (Hafalan), repeating (Ulang), understanding (Faham), al-Qur'an (Al-Qur’an), recitation (Deresan), and Adding (Ziyadah).